Structural plasticity in the dentate gyrus- revisiting a classic injury model - Perederiy, Julia V.; Westbrook, Gary L. (Frontiers in Neural Circuits, 2013)
The adult brain is in a continuous state of remodeling. This is nowhere more true than in the dentate gyrus, where competing forces such as neurodegeneration and neurogenesis dynamically modify neuronal connectivity, and can occur simultaneously. This plasticity of the adult nervous system is particularly important in the context of traumatic brain injury or deafferentation. In this review, we summarize a classic injury model, lesioning of the perforant path, which removes the main extrahippocampal input to the dentate gyrus. Early studies revealed that in response to deafferentation, axons of remaining fiber systems and dendrites of mature granule cells undergo lamina-specific changes, providing one of the first examples of structural plasticity in the adult brain. Given the increasing role of adult-generated new neurons in the function of the dentate gyrus, we also compare the response of newborn and mature granule cells following lesioning of the perforant path. These studies provide insights not only to plasticity in the dentate gyrus, but also to the response of neural circuits to brain injury.